Vapor-liquid-solid growth of one-dimensional tin sulfide (sns) nanostructures with promising field emission behavior - Suryawanshi, Sachin R.; Warule, Sambhaji S.; Patil, Sandip S.; Patil, Kashinath R.; More, Mahendra A. (ACS Applied Materials & Interfaces, 2014)
Single-crystalline ultralong tin sulfide (SnS) nanowires has been grown by a thermal evaporation technique under optimized conditions on gold-coated silicon substrates, and for the first time, field emission investigations on the SnS nanowires at the base pressure of 1 X 10(-8) mbar are reported. It has been revealed that the surface morphology of the as-synthesized SnS nanostructures is significantly influenced by the deposition temperature and duration. Structural and morphological analyses of as-synthesized SnS nanostructures have been carried out using X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). To understand the optical and electronic properties of as-synthesized SnS nanowires, ultraviolet-visible (UV-vis), photo-luminescence (PL), and X-ray photoelectron spectroscopy (XPS) studies were carried out. The SEM and TEM measurements reveal the formation of ultralong SnS nanowires, with an average diameter of 80 nm. A plausible explanation on the vapor-solid-liquid (VLS) growth mechanism based on the experimental results and reported literature has been presented. Furthermore, the field emission characteristics of the SnS nanowires are found to be superior to the other metal chalcogenide nanostructures. The synthesized SnS nanowire emitter delivers a high current density of similar to 2.5 mA/cm(2) at an applied electric field of similar to 4.55 V/mu m. The emission current stability over a period of 6 h is observed to be good. The observed results demonstrate the potential of the SnS nanowire emitter as an electron source for practical applications in vacuum nano/microelectronic devices.
Keywords: Electron emission; ID nanostructure; SnS nanowires; thermal evaporation; vapor-liquid-solid (VLS) growth